FAKTOR-FAKTOR YANG MEMPENGARUHI PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY - DECKY DERMAWAN; TITA DEITIANA (Jurnal Bisnis dan Akuntansi, 2014)
The purpose of this research is to test and analyze empirically the influence of profitability, firm size, public ownership, board of commisioner, leverage and media exposure on corporate social responsibility disclousure. This research is developed based on the previous research by Nur and Priantinah (2012). Sample in this research is mining companies which are listed in Indonesia Stock Exchange over 3 years period 2010 until 2012. This research used purposive sampling method. The statistical method used in this research is multiple regression analysis. The result of this research showed that firm size has influence toward corporate social responsibility disclousure. While, profitability, public ownership, board of commisioner, leverage and media exposure do not have influence toward corporate social responsibility disclousure.